Clinical ethics issues in HIV care in Canada: an institutional ethnographic study - Kaposy, Chris; Greenspan, Nicole R; Marshall, Zack; Allison, Jill; Marshall, Shelley; Kitson, Cynthia (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background This is a study involving three HIV clinics in the Canadian provinces of Newfoundland and Labrador, and Manitoba. We sought to identify ethical issues involving health care providers and clinic clients in these settings, and to gain an understanding of how different ethical issues are managed by these groups. Methods We used an institutional ethnographic method to investigate ethical issues in HIV clinics. Our researcher conducted in-depth semi-structured interviews, compiled participant observation notes, and studied health records in order to document ethical issues in the clinics, and to understand how health care providers and clinic clients manage and resolve these issues. Results We found that health care providers and clinic clients have developed work processes for managing ethical issues of various types: conflicts between client-autonomy and public health priorities (“treatment as prevention”), difficulties associated with the criminalization of nondisclosure of HIV positive status, challenges with non-adherence to HIV treatment, the protection of confidentiality, barriers to treatment access, and negative social determinants of health and well-being. Conclusions Some ethical issues resulted from structural disadvantages experienced by clinic clients. The most striking findings in our study were the negative social determinants of health and well-being experienced by some clinic clients – such as experiences of violence and trauma, poverty, racism, colonization, homelessness, and other factors affecting well-being such as problematic substance use. These negative determinants were at the root of other ethical issues, and are themselves of ethical concern.